(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The globalization and deepening of integration processes in the world economy presupposes a comprehensive in-depth study of agrarian business, both its internal strengths and weaknesses and its external capabilities and risks in the market. It is one of these possibilities that is to organize the agro-industrial group according to the cluster model. As a result of the analysis, serious attention will be paid to the creation of infrastructure based on advanced technologies in Uzbekistan at the next time, the introduction of the cluster method in agriculture.